PROBLEMS OF ENSURING ENERGY SECURITY AT DOMESTIC ENTERPRISES: ECONOMIC AND LEGAL ASPECTS - CHOBITOK, Viktoriia; KHOLOD, Yurii; VASIUCHENKO, Palvo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
One of the most important dominants of the modern global world is the energy system. Today, it is impossible to ensure the energy security of a country, region, or enterprise separately from international energy security. Energy security is a state of protection of energy relations, energy systems, and energy processes from threats (economic, political, legal, etc.) that can destabilize the energy situation, provoke energy conflicts, and change energy processes at various levels of management.Improving the economic and legal aspects of ensuring energy security at domestic enterprises in order to increase their efficiency is expedient to start with the energy policy within the framework of the formation of mechanisms for ensuring their energy security. These can be provisions on energy security, which must necessarily contain: elements of energy security and energy stability; analysis of the energy situation; the main energy threats that can disrupt energy stability and reduce the level of enterprise energy security risks, etc.In the conditions of the formation of a new geopolitical model of the modern world, global processes occurring in all spheres of activity are highly dynamic and determine a high level of instability. In the 21st century, the struggle for potential fuel and energy resources will intensify, which will be the basis for further instability. The study of the geopolitical features of energy development and the analysis of fuel and energy resources as a factor of global politics are of particular importance.The problem of effective use of the geopolitical potential of the fuel and energy complex is an urgent scientific problem. Economic development, political stability and the state of the natural environment in the 21st century largely depend on the development of the fuel and energy sector.Modern business conditions require increased attention to researching the issues of economic and legal aspects of ensuring energy security at domestic enterprises.However, a significant part of the economic and legal aspects of ensuring energy security at domestic enterprises is still not fully researched. This is due to the fact that currently there is an anticipatory and unpredictable rate of development of society, which is poorly predicted. The impact of active innovation and technological development can change significantly in a fairly short period of time, so it is increasingly difficult to follow dependencies and identify factors influencing the energy security of domestic enterprises.The purpose of the study of the economic and legal aspects of the issue of ensuring energy security at domestic enterprises in modern economic conditions.Problems of energy security of domestic enterprises can be quite different and affect their activity and efficiency. In today's unstable business environment, many enterprises depend on one or more energy suppliers, if problems arise that are influenced by external factors (for example, due to political or economic crises), this can lead to interruptions in the supply of energy, corresponding to downtime and disruptions in the production process .Fluctuations in the prices of energy carriers, such as gas, oil or electricity, significantly affect the additional costs of the enterprise, which leads to an increase in the prices of finished products or services, and, accordingly, reduces the level of their competitiveness.Volatility in energy prices is a significant problem for domestic enterprises, as it affects costs, budgeting and financial stability. This volatility can be caused by a variety of factors, including market conditions, political events and natural disasters.Problems that can negatively affect the change in energy prices are related to fluctuations in energy prices on world markets under the influence of global economic conditions, changes in supply and demand, as well as events such as conflicts, sanctions, trade wars, etc.Considering Ukraine's integration into the European and international energy market, adaptation to European norms and standards is critically important for all business entities. This process is related to the harmonization of Ukrainian legislation to European standards, as well as the implementation of international practices in the management of energy resources and ensuring energy security at domestic enterprises.In modern economic conditions characterized by high uncertainty and dynamic changes, legal regulation of energy security is an important tool for reducing risks, supporting investments, ensuring stability and sustainable development of enterprises. The formation of effective mechanisms for ensuring energy security at domestic enterprises requires a comprehensive approach that covers technical, economic, legal, social and organizational aspects. This makes it possible to reduce risks, increase the efficiency of the use of energy resources and ensure the stable operation of the enterprise in the conditions of modern challenges.As a result of the research, it was identified that one of the most important dominants of the modern global world is the energy system, the essence of which is the protection of energy relations, energy systems and energy processes from threats (economic, political, legal, etc.) that can destabilize the energy situation, provoke energy conflicts, change energy processes at different levels of management.To improve the economic and legal aspects of ensuring energy security at domestic enterprises in order to increase their efficiency, it is advisable to start with energy policy within the framework of the formation of mechanisms for ensuring their energy security.Fluctuations in the prices of energy carriers, such as gas, oil or electricity, significantly affect the additional costs of the enterprise, which leads to an increase in the prices of finished products or services, and, accordingly, reduces the level of their competitiveness.Volatility in energy prices is a significant problem for domestic enterprises, as it affects costs, budgeting and financial stability. This volatility can be caused by a variety of factors, including market conditions, political events and natural disasters.The article examines the economic and political aspects of ensuring energy security at domestic enterprises, which is the basis for the formation of mechanisms for ensuring energy security at domestic enterprises.It was determined that a comprehensive approach to solving these problems and the implementation of the specified solutions can significantly increase the level of energy security at domestic enterprises and ensure their stable development in the conditions of modern economic and political instability.
Keywords: energy security; energy tariffs; economic and legal aspects; energy resources; domestic enterprises; development; instability